Association of IL-6 and TGF-β Gene Polymorphisms with the Risk of Thoracolumbar Osteoporotic Vertebral Compression Fractures - Xiong Y; He Y; Peng Y; Geng Y (Dove Medical Press, 2022)
Yi Xiong,1 Ye He,2 Yan Peng,3 Yun Geng4 1Department of Orthopaedic, The Central Hospital of Enshi Tujia and Miao Autonomous Prefecture, Hubei, People's Republic of China; 2Department of Preventive Treatment of Diseases,Shaanxi Meixian Hospital of Traditional Chinese Medicine, Shaanxi, People's Republic of China; 3Department of Medical Examination, Yili Kazak Autonomous Prefecture Hospital of Traditional Chinese Medicine, Xinjiang, People's Republic of China; 4Department of Pharmacology, Shandong First Medical University and Shandong Academy of Medical Sciences, Shandong, People's Republic of ChinaCorrespondence: Yun Geng, Tel/Fax +86-531-59556066, Email gengyunsd@163.comPurpose: Osteoporotic vertebral compression fracture (OVCF) is a common disease in the elderly, and genetic factors play a key role in its occurrence. The present study was conducted to investigate the association between interleukin-6 (IL-6) and the transforming growth factor (TGF-β) gene polymorphisms and the occurrence of thoracolumbar OVCF.Patients and Methods: This case-control study recruited 146 patients with OVCF and 144 osteoporosis patients as the control group. Genotypes of the IL-6 rs1800796 and TGF-β rs1982073 were analyzed by sequencing. Genotype distribution and allelic frequencies were investigated by the χ2 test. Odds ratios (OR) and 95% confidence intervals (CI) evaluated the relationship of IL-6 or TGF-β polymorphism and OVCF susceptibility.Results: Allele G and genotype GG of IL-6 rs1800796 was more frequent in patients with OVCF (40.07% vs.28.47%; 19.18% vs.7.64%) compared with controls. GG genotype (OR=3.394, 95% CI=1.560- 7.385, P < 0.001) and G allele (OR=1.680, 95% CI=1.187- 2.376, P < 0.001) of IL-6 rs1800796 was significantly associated with increased risk of OVCF. What is more, CT and TT genotypes (41.78 vs.51.39; 19.86 vs.26.39) and allele T (40.75 vs 52.08) of TGF-β rs1982073 were less frequent in OVCFs, more common in controls and protective against OVCF risk (OR=0.436, 95% CI=0.228- 0.835, P = 0.012; OR=0.615, 95% CI=0.443- 0.855, P = 0.004).Conclusion: Our results suggest that the G allele and GG genotype of IL-6 rs1800796 may contribute to increased susceptibility to OVCF in elderly Chinese. In contrast, CT and TT genotypes and the T allele of TGF-β rs1982073 may contribute to lower susceptibility of OVCF.Keywords: OVCF, IL-6, TGF-β, gene polymorphisms